2011
DOI: 10.1097/eja.0b013e32834088c4
|View full text |Cite
|
Sign up to set email alerts
|

Level of agreement between heart rate variability and pulse rate variability in healthy individuals

Abstract: Our data show that PRV derived from non-invasive blood pressure waveforms corresponds well with traditional HRV derived from ECG. These results indicate that under standard conditions, blood pressure waveforms may replace HRV in healthy individuals and that the use of PRV in the peri-operative setting should be further evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 24 publications
4
27
0
Order By: Relevance
“…The Nexfin HD is a novel, noninvasive arterial blood pressure monitor, which has recently been validated with respect to blood pressure and cardiac output [12,15,16]. We recently showed that Nexfin HD reproducibly reflects the classical Ewing autonomic function test battery and can be used to measure pulse rate variability as an alternative for heart rate variability [20,21]. Studies comparing the applicability of different noninvasive blood pressure measurement devices in autonomic function testing are however lacking.…”
Section: Discussionmentioning
confidence: 98%
“…The Nexfin HD is a novel, noninvasive arterial blood pressure monitor, which has recently been validated with respect to blood pressure and cardiac output [12,15,16]. We recently showed that Nexfin HD reproducibly reflects the classical Ewing autonomic function test battery and can be used to measure pulse rate variability as an alternative for heart rate variability [20,21]. Studies comparing the applicability of different noninvasive blood pressure measurement devices in autonomic function testing are however lacking.…”
Section: Discussionmentioning
confidence: 98%
“…We used beat-to-beat pressure curves to derive pulse interbeat intervals for HRV analysis rather than RR-intervals derived from an ECG, which is considered the gold-standard [12]. However, pulse derived HRV have been compared to HRV derived from ECG in several studies and have demonstrated sufficient accuracy in subjects at rest [2931], although short term variability such as the HF component may be overestimated with standing and exercise due to variations in pulse transit time [31]. An overestimation of the HF component during standing may have influenced our results, but an increase in HF during standing was not observed in the preoperative test and thus the postoperative postural decrease in the LF/HF ratio cannot be explained by the inherent limitations of pulse derived HRV analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic function is mainly represented in the very low‐frequency band (0.00–0.04 Hz), which is related to fluctuations in vasomotor tone and is associated with thermoregulation, whereas the high‐frequency band (0.12–0.40 Hz) may represent the efferent vagal activity and is related to respiratory activity. The low‐frequency band (0.04–0.12 Hz) may be a representative of parasympathetic as well as sympathetic innervation, and is associated with the baroreceptor reflex (Table ) .…”
Section: Diagnosis Of Autonomic Neuropathymentioning
confidence: 99%
“…Two minutes after standing up quickly, systolic blood pressure is measured again. In normal healthy subjects, the drop in systolic blood pressure is < 10 mmHg . A fall in systolic pressure of 20 mmHg or more indicates impaired cardiovascular autonomic circulatory function (Table ).…”
Section: Diagnosis Of Autonomic Neuropathymentioning
confidence: 99%